2014
DOI: 10.3345/kjp.2014.57.6.264
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of acute necrotizing encephalopathy in related to involving the brain stem of single institution in Korea

Abstract: PurposeAcute necrotizing encephalopathy (ANE) is a fulminant disease of the brain characterized by bilateral thalamic lesions, and is prevalent among children in East Asia. The prognosis of ANE is usually poor with a high mortality rate and neurological sequelae. This study aimed to delineate the clinical characteristics and prognostic factors of ANE.MethodsWe retrospectively analyzed clinical data of 399 pediatric patients with encephalitis who were admitted to Samsung Medical Center from December 1998 to Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 16 publications
2
20
1
3
Order By: Relevance
“…[ 6 ] Our patient had brainstem involvement, and it leads to brain death while a report from Korea showed that 40% of their patient with brainstem involvement expired during the acute illness and another 30% developed severe neurological impairment. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Our patient had brainstem involvement, and it leads to brain death while a report from Korea showed that 40% of their patient with brainstem involvement expired during the acute illness and another 30% developed severe neurological impairment. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al examined the thalamus in six acute necrotizing encephalopathy patients, finding hyperintensity on DWI and a low ADC in four patients, hypointensity on DWI and a high ADC in one patient, and no change in DWI or ADC in one patient. 3 Brainstem involvement, rather than findings for DWI and ADC, suggests poor outcome. 3 Influenza and human herpesvirus-6 are representative pathogens for acute necrotizing encephalopathy.…”
Section: Discussionmentioning
confidence: 98%
“…3 Brainstem involvement, rather than findings for DWI and ADC, suggests poor outcome. 3 Influenza and human herpesvirus-6 are representative pathogens for acute necrotizing encephalopathy. 4 Our clinical observations suggested human herpesvirus-6 as the most likely pathogen for the fulminant encephalopathy in this patient.…”
Section: Discussionmentioning
confidence: 98%
“…24 In children with acute necrotising encephalitis, extensive and marked T2-weighted hyperintense signal changes in the brainstem with restricted diffusion or haemorrhage are associated with mortality. 25 Extensive damage in the medulla and pons is a sign of profound progression of disease, as severe brainstem dysfunction may lead to neurogenic oedema, respiratory insufficiency, cardiopulmonary collapse, and mortality. 25 Nonetheless, the lack of association between cerebellar lesions and adverse neurological outcome may indicate that MRI has no prognostic value in acute cerebellitis.…”
Section: Discussionmentioning
confidence: 99%
“…25 Extensive damage in the medulla and pons is a sign of profound progression of disease, as severe brainstem dysfunction may lead to neurogenic oedema, respiratory insufficiency, cardiopulmonary collapse, and mortality. 25 Nonetheless, the lack of association between cerebellar lesions and adverse neurological outcome may indicate that MRI has no prognostic value in acute cerebellitis. 26 Further studies are needed to elucidate the patterns of association.…”
Section: Discussionmentioning
confidence: 99%